2017
DOI: 10.7554/elife.22058
|View full text |Cite|
|
Sign up to set email alerts
|

Palmitoylated SCP1 is targeted to the plasma membrane and negatively regulates angiogenesis

Abstract: SCP1 as a nuclear transcriptional regulator acts globally to silence neuronal genes and to affect the dephosphorylation of RNA Pol ll. However, we report the first finding and description of SCP1 as a plasma membrane-localized protein in various cancer cells using EGFP- or other epitope-fused SCP1. Membrane-located SCP1 dephosphorylates AKT at serine 473, leading to the abolishment of serine 473 phosphorylation that results in suppressed angiogenesis and a decreased risk of tumorigenesis. Consistently, we obse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
30
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(34 citation statements)
references
References 80 publications
4
30
0
Order By: Relevance
“…In fact, the only genes whose expression levels have been reported to be altered by knockdown of SCP1 are all controlled by REST, which is consistent with the regulatory action of SCP1 in the REST neuronal silencing program (24). A recent report also showed that SCP1 and its homologues can be targeted to the plasma membrane through palmitoylation in different nonneuronal tumor cell lines (43). However, in non-neuronal tumors there are often significantly decreased amounts of functional REST protein (44,45), making them poor targets for SCP1 inhibitors.…”
Section: Scp1 Controls the Stability Of Restsupporting
confidence: 68%
See 1 more Smart Citation
“…In fact, the only genes whose expression levels have been reported to be altered by knockdown of SCP1 are all controlled by REST, which is consistent with the regulatory action of SCP1 in the REST neuronal silencing program (24). A recent report also showed that SCP1 and its homologues can be targeted to the plasma membrane through palmitoylation in different nonneuronal tumor cell lines (43). However, in non-neuronal tumors there are often significantly decreased amounts of functional REST protein (44,45), making them poor targets for SCP1 inhibitors.…”
Section: Scp1 Controls the Stability Of Restsupporting
confidence: 68%
“…Neuronal tumors such as glioblastomas on the other hand can have abnormally high amounts of REST protein, which correspond with high levels of SCP1 (10,11), making them ideal targets for SCP inhibitors. SCP1 was also found to suppress tumorigenesis in a lung cancer model (43), but we suspect this function would play a minor role in cancers like glioblastomas due to their aggressive nature. Thus, whereas it is important to explore the possibility of SCP shuttling in neuro-…”
Section: Scp1 Controls the Stability Of Restmentioning
confidence: 93%
“…Recent reviews have summarized the roles of S-acylation in synaptic plasticity, immunological synapses, host-pathogens interactions, and membrane trafficking (Fukata and Fukata 2010;Aicart-Ramos et al 2011;Blanc et al 2013;Chamberlain and Shipston 2015;Fukata et al 2016;Globa and Bamji 2017), therefore, these subjects will not be covered here. Additionally, recent studies highlighted the role of protein S-acylation in modulating membrane curvature in Influenza A virus assembly (Chlanda et al 2017); regulating the shuttling of SCP1 between the nucleus and other subcellular compartments (Liao et al 2017); among others. This section provides selected recent examples illustrating important regulatory roles of protein S-acylation in several physiological processes.…”
Section: Physiological Relevance Of S-acylationmentioning
confidence: 99%
“…This suggests that CTDSP1 can potentially attenuate TWIST1 and antagonize cancer progression [16]. CTDSP1 has been known as a nuclear phosphatase, but in a recent study, researchers found that it is localized to the plasma membrane by lipid modifications [79]. This is also fashionably related to the tumor growth and N-terminal modification abilities of CTDSP1.…”
Section: Ctdsp1 As An Emerging Targetmentioning
confidence: 99%